PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. INKABIZ INDONESIA - Husain, Moh. Ali; Anjani, Septi Rostika (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to determine the effect of training and work discipline on employee performance at PT. Inkabiz Indonesia. Training and work discipline are two important factors in improving the quality of human resources and achieving company targets. This research uses a quantitative method with an associative approach. The sampling technique employed Slovin’s formula from a population of 108 people, resulting in 85 respondents as the sample. Data were collected through questionnaires. Data analysis included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²), with the assistance of SPSS version 27. The results show that the training variable (X₁) has no positive and significant effect on employee performance, with a significance value of 0.223 > 0.05. In contrast, the work discipline variable (X₂) has a positive and significant effect on employee performance, with a significance value of 0 < 0.05. The simultaneous test (F-test) indicates that training and work discipline together have a significant effect on employee performance, with a significance value of 0.001 < 0.05. The coefficient of determination (R²) of 0.598 indicates that 59.8% of the variation in employee performance is influenced by training and work discipline, while the remaining 40.2% is influenced by other variables outside this study.